The Value of Routine Intravenous Tranexamic Acid in Total Hip Arthroplasty: A Preliminary Study - J. Chin; J. Blackett; D. C. Kieser; C. Frampton; G. Hooper (Advances in Orthopedics, 2020)
Objective. To determine the effect on the need for transfusion when intravenous tranexamic acid (TXA) is administered intraoperatively in patients undergoing total hip arthroplasty (THA). Method. A prospective, double blinded, randomised control trial of 88 patients undergoing THA was randomly allocated to receive 1 g of intravenous TXA or normal saline on induction of anaesthesia. All patients received spinal anaesthesia. The primary outcome measure was transfusion rate, and the secondary outcomes were intraoperative blood loss, haemoglobin levels, length of hospital stay, functional scores, and thromboembolic complications. Results. 19.0% of patients given TXA required a blood transfusion, compared with 20.5% given placebo (p=0.87). Secondary outcomes included mean intraoperative blood loss, which was 536.5 ml in the TXA group and 469.8 ml in the placebo group (p=0.276). Day 1 haemoglobin levels were 108.9 g/l in the TXA group versus 104.3 g/l in the placebo group (p=0.114). Day 4 haemoglobin levels were 105.0 g/l and 99.8 g/l, respectively (p=0.130). The mean length of stay in those who received TXA was 4.3days, compared with 4.8days in those given placebo (p=0.20). The Oxford Hip Score showed a mean improvement over a 1-year period of 25.9 points in those who received TXA, compared with 26.7 points in those who received placebo (p=0.679). There were two treatment emergent adverse events: a pulmonary embolism (TXA) and a myocardial infarction (placebo). Conclusions. 1 g IV TXA administered on induction did not significantly reduce the need for blood transfusion, postoperative blood loss, functional scores, or the length of stay in patients undergoing THA. This trial is registered with ACTRN12610001065088.